Emotion, Value, and the Normativity of Fittingness - Lewis, Max (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2024)
I sketch evidence for a normative view of fittingness that poses a challenge to the nonnormative view of fittingness that Christine Tappolet defends in Philosophy of Emotion (2023). This challenge is important given that fittingness is crucial to her view of evaluative features and thus to her view of emotions as representations of evaluative features.